SENIOR LIVING SEBAGAI REKONSTRUKSI KEHIDUPAN LANSIA DI PENJARINGAN - Evelyn Augustine Tjitra; F. Tatang H. Pangestu (Jurusan Arsitektur dan Perencanaan, 2022)
The welfare of the elderly is still very neglected, especially in Penjaringan which is a sub-district in North Jakarta with the largest elderly population in the capital. The degradation of the quality elderly life in Penjaringan has a fairly high urgency, especially in maintaining the mental health of the seniors. The absence of activities or busyness in their daily lives creates a passive lifestyle from the lack of activities, participation and social interactions needed on a daily basis. The elderly in Penjaringan who lack the opportunity or forum for activities show that their quality of life is getting worse and leads to a decline in the psychological condition or mental health of the elderly. To help the elderly achieve a prosperous life, this project uses an urban acupuncture approach with a method that analyzes and observes the daily life of the elderly in Penjaringan, seeks to improve the quality of life of the elderly and provide welfare with programs that focus on mental health and active participation of the elderly. The project's local intervention in Penjaringan is to create a residential and social environment that supports the principle of the elderly as dignified human beings with an active aging approach. The intervention starts from improving the lifestyle of the elderly who were previously not ideal and passive, then providing a forum for channeling hobbies and activities in individual and social activities to build and support the elderly to achieve a prosperous life. Keywords: Active; Quality of Life; Elderly; Social Abstrak Kesejahteraan lansia masih sangat kurang diperhatikan terutama di Penjaringan yang merupakan sebuah kecamatan di Jakarta Utara dengan populasi lanjut usia terbanyak di Ibukota. Degradasi kualitas hidup lansia di Penjaringan memiliki urgensi yang cukup tinggi dalam menjaga kesehatan mental para senior tersebut. Tidak adanya kegiatan atau kesibukan dalam kesehariannya menciptakan gaya hidup pasif dari kurangnya kegiatan, partisipasi serta interaksi sosial yang dibutuhkan sehari-hari. Lansia di Penjaringan yang kurang memiliki kesempatan atau wadah untuk beraktivitas menunjukkan kualitas hidup yang semakin memburuk dan berujung pada penurunan kondisi psikologis atau kesehatan mental lansia tersebut. Untuk membantu para lansia mencapai kesejahteraan hidup, proyek ini melalui pendekatan urban acupuncture dengan metode yang menganalisis dan mengamati keseharian lansia di Penjaringan, berusaha meningkatkan kualitas hidup lansia serta memberikan kesejahteraan dengan program yang berfokus pada kesehatan mental dan pastisipasi aktif lansia. Intervensi lokal proyek dalam Penjaringan yaitu menciptakan lingkungan tempat tinggal dan sosial yang mendukung prinsip lansia sebagai manusia yang bermartabat dengan pendekatan active ageing. Intervensi tersebut dimulai dari perbaikan pola hidup lansia yang sebelumnya belum ideal dan pasif, kemudian memberikan wadah untuk menyalurkan hobi serta aktivitas dalam kegiatan individu maupun sosial untuk membangun dan mendukung lansia mencapai kesejahteraan hidup.